Gender differences in objectively assessed physical activity in asthmatic and non-asthmatic children - Yiallouros, Panayiotis K.; Economou, Mary; Kolokotroni, Ourania; Savva, Savvas C.; Gavatha, Marina; Ioannou, Phivos; Karpathios, Themistoclis; Middleton, Nicos (My University, 2015)
Objective: To compare objectively assessed physical activity levels, between asthmatic children and non-asthmatic controls. Methods: From a random community sample of 794 children aged 8-9 years, in a case-control design, 104 children with ever doctor's diagnosis of asthma and 99 non-asthmatic controls were recruited and had assessment of physical activity with biaxial accelerometers for 7 days. Results: Children with active (also reporting at least one episode of wheezing in the last 12 months) and inactive (no wheezing in past 12 months) asthma appeared to have similar physical activity and sedentary activity levels compared to non-asthmatic children. However, girls with active asthma had significantly lower moderate-to-vigorous physical activity (MVPA) levels than their peers with adjusted geometric mean ratio of 0.59 (95% CI: 0.369, 0.929, P-value=0.024). No difference in physical and sedentary activity levels was observed between asthmatic and non-asthmatic boys. The difference between genders in the comparison of MVPA levels in asthmatics and controls was statistically significant (P-value of likelihood ratio test [LRT] for effect modification by gender=0.034). Conclusions: Unlike boys, girls with active asthma appear to be less active than their healthy peers, and this gender difference might explain the inconsistent evidence from previous reports on physical activity levels in asthmatic children. Further studies are needed to confirm the gender interaction in the childhood asthma-physical activity relation and the implications on current guidelines for physical exercise prescriptions in asthmatic children.
Keywords: Accelerometer; Cyprus; Gender interaction